Hubungan Minat Baca dan Berpikir Kritis dengan Kemampuan Menulis Ilmiah: Penelitian Korelasional di SMPN 255 Jakarta Timur - Supriyati Supriyati (UHAMKA Graduate School Thesis Abstract Collection, 2016)
This research aimed at determining the correlation between Reading Interest and Critical Thinking also to identify weather there is an interaction of both toward the ability of scientific writing. While critical thinking in this case is a process of thinking systematically in deciding the truth and exactness as well as confection based on logic, facts and language. The research was conducted at the State Junior High School 255, Duren Sawit, East Jakarta in 2013. The population is the students of grade IX of the State Junior High School 255, Duren Sawit, East Jakarta, with samples taken as many as 71 students randomly. The method used is descriptive with correlation technique. The concept of research used descriptively and inferentially with analyze of double regression an simple correlation, double correlation and partial correlation at the significance level α = 0,05. The result shows there is a positive correlation between reading interest with scientific writing. There is a positive correlation between critical thinking with ability of scientific writing. There is a positive correlation altogether among reading interest and critical thinking with ability on scientific writing. Based on the findings in this research, it is stated that the writing ability can be increased by the students through the efforts of increasing reading interest and critical thinking.